Skrining Senyawa Kimia dan Uji Aktivitas Sitotoksik Ekstrak Etanol Teripang Kridou Bintik (Bohadschia argus Jeager) Asal Pantai Harlem Kabupaten Jayapura, Papua - Apianus Kilungga; Linus Y. Chrystomo; Puguh Sujarta (Jurnal Biologi Papua, 2019)
The Bohadschia argus Jeager contains bioactive compounds that have the potential as antibiotics, antibacterial, antitumor, anticoagulants and anesthetics and alleviate cancer. This study aims to determine the content of chemical compounds group and to test the cytotoxic activity of ethanol extract of Bohadschia argus Jeager. The method for determining the group of chemical compounds was used the color reaction and precipitation using chemical reagents. The method for testing cytotoxic activity using the Brine Shimp Lethality Test (BSLT), this method commonly was used to test the safety of the use of natural ingredients as traditional medicine. The results of screening of the chemical compound group of  Bohadschia argus Jeager extract showed that the extract contained a lot of alkaloids secondary metabolites and few saponins. The results of testing of cytotoxic activity showed LC50 value of 878.22 ppm. Base on the results of this study it can be concluded that the ethanol extract of Bohadschia argus Jeager has significant cytotoxic activity against Artemia salina Leach, so it can be considered as a chemotherapeutic agent.   Key words: Screening, chemical compounds, ethanol extract, B. argus, BSLT.